(Citric acid–co–polycaprolactone triol) polyester: A biodegradable elastomer for soft tissue engineering - Thomas, Lynda V. (Landes Bioscience, 2011)
Tissue engineering holds enormous challenges for materials science, wherein the ideal scaffold to be used is expected to be biocompatible, biodegradable and possess mechanical and physical properties that are suitable for target application. In this context, we have prepared degradable polyesters in different ratios by a simple polycondensation technique with citric acid and polycaprolactone triol. Differential scanning calorimetry indicated that the materials were amorphous based the absence of a crystalline melting peak and the presence of a glass transition temperature below 37°C. These polyesters were found to be hydrophilic and could be tailor-made into tubes and films. Porosity could also be introduced by addition of porogens. All the materials were non-cytotoxic in an in vitro cytotoxicity assay and may degrade via hydrolysis to non-toxic degradation products. These polyesters have potential implications in the field of soft tissue engineering on account of their similarity of properties.